The international treaty on plant genetic resources for food and agriculture: experiences of international institutions with the implementation of the agreements with the Governing Body under Article 15 of the Treaty - CGIAR; Food and Agriculture Organization of the United Nations (2011)
At its Third Session, the Governing Body noted that at its Second Session it endorsed that interpretative footnotes or series of footnotes would be included to relevant provisions of the Standard Material Transfer Agreement (SMTA) for transfers of non-Annex I material collected before the entry into force of the International Treaty to be used by the International Agricultural Research Centres (IARCs) of the Consultative Group on International Agricultural Research. The Governing Body also noted that the IARCs commenced using the Standard Material Transfer Agreement with footnotes on 1 February 2008, and that the IARCs still have only limited experience with the use to date. The Governing Body further noted that although the IARCs have used the SMTA for a relatively short time, the impression of the Centres is that the SMTA is attracting increasing acceptance by potential recipients as they become more familiar with its terms. The Governing Body decided that it would further review these measures at its Fourth Session.